2007
DOI: 10.1002/path.2163
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary dysfunction and impaired granulocyte homeostasis result in poor survival of Jam‐C‐deficient mice

Abstract: Jam-C(-/-) mice exhibit growth retardation and multilobular pneumonia concomitant with poor survival of the mice under conventional housing conditions. The deficient mice present a mega-oesophagus and have altered airway responsiveness. In addition, the number of circulating granulocytes is increased in Jam-C(-/-) mice as compared to control animals. These phenotypes probably reflect the different functions of JAM-C expressed by endothelial and mesenchymal cells. Indeed, the deregulation in the number of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 34 publications
8
58
1
1
Order By: Relevance
“…The latter was postulated as a potential novel role for JAM-C in regulation of leukocyte accumulation after the observations that JAM-C-deficient mice exhibited an increase in peripheral blood neutrophils after an inflammatory challenge. 64 This finding was not a consequence of increased neutrophil replenishment from the animal's bone marrow or other lymphatic tissues as assessed in a passive transfer study. Briefly, the intravenous injection of labeled wild-type neutrophils into JAM-C-deficient recipients also resulted in a high circulation level after an inflammatory challenge.…”
Section: An Emerging Novel Function Of Jam-cmentioning
confidence: 79%
See 2 more Smart Citations
“…The latter was postulated as a potential novel role for JAM-C in regulation of leukocyte accumulation after the observations that JAM-C-deficient mice exhibited an increase in peripheral blood neutrophils after an inflammatory challenge. 64 This finding was not a consequence of increased neutrophil replenishment from the animal's bone marrow or other lymphatic tissues as assessed in a passive transfer study. Briefly, the intravenous injection of labeled wild-type neutrophils into JAM-C-deficient recipients also resulted in a high circulation level after an inflammatory challenge.…”
Section: An Emerging Novel Function Of Jam-cmentioning
confidence: 79%
“…Briefly, the intravenous injection of labeled wild-type neutrophils into JAM-C-deficient recipients also resulted in a high circulation level after an inflammatory challenge. 64 Conventional models of increased neutrophil numbers in the blood during inflammation would predict this finding as a result of reduced recruitment. However, in vitro studies with cocultures of human peripheral blood neutrophils on activated endothelium under shear flow conditions have shown that neutrophil capture, firm adhesion, and transmigration is JAM-C-independent.…”
Section: An Emerging Novel Function Of Jam-cmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout models of junctional adhesion molecules and integrins can affect the immune response in mice, predisposing them to infection or protecting them from lung injury. Junctional adhesion molecule 3 (JAM3) knockout mice are predisposed to pneumonia sec- (225), (226), (227), (228), (229), (230), (231), (232), (233), (234), (235), (236), (237 ondary to an altered immune response in the airway (38). Interestingly, this enhanced inflammatory response in integrin a v (ITGAV) and integrin b 6 (ITGB6) knockout mice can lead to possible protection from pulmonary fibrosis (39)(40)(41).…”
Section: Targeted Deletions Of Most Adhesion Molecules Do Not Results mentioning
confidence: 99%
“…Par ailleurs, la perte de l'activité adhésive de JAM-C exprimée par l'endothélium résulte en une susceptibilité accrue des souris Jam-C -/-aux infections opportunistes et en une perte de la régulation de l'homéostasie des neutrophiles sanguins [10]. Mais le résultat le plus remarquable est le phé-notype de neuropathie héréditaire avec hypersensibilité à la pression (HNPP) que présentent les souris déficientes leur interaction avec des partenaires cytoplasmiques jouant essentiellement un rôle dans la polarité cellulaire [2].…”
unclassified